Artificial neural network for modeling coagulant dosing for water treatment plants - Olanrewaju, Rashidah Funke; Muyibi, Suleyman Aremu; Salawudeen, T. Olalekan; Aibinu, Abiodun Musa (2011)
Coagulation-flocculation process remains a very essential part in the water treatment chain. It involves both physical and chemical phenomena and hence susceptible to high percentage of errors due to human factors. In order to reduce this percentage error and obtain optimal treatment efficiency, an intelligent coagulant dosing based on Artificial Neural Network (ANN) was proposed. Design of the Coagulant dosing using processed Moringa Oleifera seed as coagulant was achieved through ANN that helps in water quality forecast and soft measure. Experimental results with simulated and real data show that the newly developed system is able to accurately predict coagulant dosage needed in water treatment for a small size rural community. The correlation between actual and ANN estimation of coagulant dosing model is 0.97 of 1.00. This high Correlation of coefficient indicates that the NN model is a perfect match. Such coagulant dosing based ANN will be a useful method to address most errors common in water treatment cause by human factors.